Towards Energy Efficient Onsite Wastewater Treatment - Mirra, Renata; Ribarov, Christian; Valchev, Dobril; Ribarova, Irina (Salehan Institute of Higher Education, 2020)
The objective of this work is to demonstrate that some weaknesses of the onsite packaged WWTP associated with high operational costs and energy inefficiency could be overcome by improved management. The research methodology consists of series of batch studies with sludge from municipal or onsite WWTP, which simulate different working regimes of the onsite WWTPs â€“ daily operation, toilet flushing and dishwasher machine. A simple classical tool, Oxygen Uptake Rate (OUR) is used to prove the hypothesis that regardless the specificity of the onsite WWTPs, namely the irregularity of the flow and load, three parameters follow similar increasing and decreasing trends â€“ inflow rate, inflow pollution load and oxygen demand in the reactor. The literature review has not shown research publication about applicability of (OUR) for management of onsite WWTPs, but has shown experience and knowledge with municipal WWTPs, which were utilized in our study. The results prove that when there is no wastewater generation in the household, the (OUR) in the reactor is very low, 0.0007 to 0.0015 mg/l.s, thus do not require high oxygen supply. However, when wastewater flushes into the onsite WWTP, the oxygen demand increases rapidly and (OUR) reaches the range of 0.0040 to 0.0063 mg/l.s depending on the type and the quantity of the incoming substrate (pollution load). These results, if verified in filed experiments will enable optimization of the energy use during onsite WWTP operation.Â The suggestion is that the oxygen supply in the reactor should be adjusted according to the demand, respectively proportional to the inflow rate. In addition to the benefit of saving energy, the comprehensive sensors for dissolved oxygen monitoring, which require qualified maintenance could be avoided and replaced by simple sensors for level, which are anyway part of the equipment of most of the onsite packaged WWTP.